Vitamin D, Vitamin B9 (Folic Acid) and Vitamin B12 Status in Bipolar Disorder: Associations with Symptom Severity and Course of Illness - Styczyńska, Małgorzata; Wojewódzki, Maciej; Cyrzan, Alicja; Zalewski, Jakub; Zysk, Adam; Ząbek, Mateusz; Iwanowska, Martyna; Flis, Beata; Goss, Adrian; Fronczak, Bartosz (Journal of Education, Health and Sport, 2026)
Background: Bipolar disorder (BD) is a chronic mood disorder associated with substantial functional impairment and elevated suicide risk. Nutritional psychiatry has highlighted potential links between vitamin D, folate (vitamin B9), vitamin B12, and one-carbon metabolism (including homocysteine) and affective symptom burden, yet BD-specific evidence remains heterogeneous. Aim: To organize and critically synthesize evidence on the relationship between vitamin D status (25[OH]D) and B-group vitamins-particularly folate (B9) and vitamin B12-and the clinical phenotype of BD, including symptom severity, illness phase, course features, cognition, suicidality-related outcomes, and the effects of supplementation where available. Material and methods: All data were collected from publicly available sources. This article’s databases were accessed via PubMed/MEDLINE and the Cochrane Library. Summary: Current evidence supports frequent vitamin D insufficiency in BD but does not demonstrate an evidence-based therapeutic effect of vitamin D supplementation on bipolar depressive symptoms. Folate, vitamin B12, and homocysteine findings more consistently relate to bipolar depression and cardiometabolic comorbidity, while supplementation data remain preliminary and insufficient for routine adjunctive use beyond documented deficiency. In clinical practice, assessment and correction of vitamin D, folate, and especially vitamin B12 abnormalities should be considered as part of comprehensive medical care in BD, with vitamin B12 testing having particular value when presentations are atypical or medically suggestive.